State support of bioenergy in Ukraine: legal problems - Годованюк, Андрій Йосипович; Годованюк, А. Й.; Годованюк, Андрей Иосифович; Hodovaniuk, Andrii Y.; Григор’єва, Христина Антонівна; Григор’єва, Х. А.; Григорьева, Кристина Антоновна; Hryhorieva, Khrystyna A.; Платонова, Євгенія Олегівна; Платонова, Є. О.; Платонова, Евгения Олеговна; Platonova, Yevheniia O.; et al. (Universidad de la Amazonia, 2020)
The article is devoted to the study of state support in the field of bioenergy production in Ukraine. It is mentioned, that it is still not clear the legal nature of agricultural bioenergy relations. However, it is quite clear that relations on state support of bioenergy production (in terms of production of biofuels from agricultural raw materials) belong to the subject of agroprotective law and are regulated by it. This is due to the fact that: first, the objects of bioenergy relations are biomass and biofuels, which are agricultural products; secondly, the subjects of bioenergy relations are mainly agricultural producers or processors; thirdly, the content of bioenergy relations is in the production and processing of agricultural products. That is, bioenergy relations at the stages of production (formation) of biomass and its processing into biofuels constitute a type of agricultural activity, the state support of which is regulated by agroprotective law. It is revealed that in terms of state support should be taken such measures as: support of processing of actually produced agricultural products by its producer; support of creation of agricultural processing cooperatives; support of bioenergy production, which is based on the process of processing biomass into biofuels. Improvement of agroprotective legislation in this area should occur by: a) foreseeing universal legal mechanisms to support processing activities in the Law of Ukraine "On state support of agriculture of Ukraine"; b) addition to the Law of Ukraine "On agricultural cooperation" of agroprotective provisions on agricultural processing cooperatives; c) adoption of the Law of Ukraine "On production and sale of biofuels".

Стаття присвячена дослідженню державної підтримки виробництва біоенергетики в Україні. Зазначається, що досі не зрозуміла правова природа відносин у галузі біоенергетики сільського господарства. Однак цілком зрозуміло, що відносини щодо державної підтримки біоенергетичного виробництва (у частині виробництва біопалива із сільськогосподарської сировини), безумовно, входять до предмету агропротекційного права та регулюються ним. Це пояснюється тим, що: по-перше, об’єктами біоенергетичних відносин виступають біомаса та біопаливо, які є сільськогосподарською продукцією; по-друге, суб’єктами біоенергетичних відносин переважно виступають виробники сільськогосподарської продукції або її переробники; по-третє, зміст біоенергетичних відносин полягає у виробництві та переробці сільськогосподарської продукції. Тобто біоенергетичні відносини на етапах виробництва (утворення) біомаси та її переробки в біопаливо складають різновид сільськогосподарської діяльності, державна підтримка якої регулюється агропротекційним правом. Виявлено, що з точки зору державної підтримки слід вживати таких заходів, як: підтримка здійснення переробки власно виробленої сільськогосподарської продукції її виробником; підтримка утворення сільськогосподарських переробних кооперативів; підтримка біоенергетичного виробництва, в основі якого лежить процес переробки біомаси в біопаливо. Удосконалення агропротекційного законодавства у цій сфері має відбуватися шляхом: а) передбачення універсальних правових механізмів підтримки переробної діяльності у Законі України «Про державну підтримку сільського господарства України»; б) доповнення Закону України «Про сільськогосподарську кооперацію» агропротекційними положеннями щодо сільськогосподарських переробних кооперативів; в) прийняття Закону України «Про виробництво і реалізацію біопалива».

Статья посвящена исследованию государственной поддержки производства биоэнергетики в Украине. Отмечается, что до сих пор не понятна правовая природа отношений в области биоэнергетики сельского хозяйства. Однако совершенно ясно, что отношения государственной поддержки биоэнергетического производства (в части производства биотоплива из сельскохозяйственного сырья), безусловно, входят в предмет агропротекционного права и регулируются им. Это объясняется тем, что: во-первых, объектами биоэнергетических отношений выступают биомасса и биотопливо, которые являются сельскохозяйственной продукцией; во-вторых, субъектами биоэнергетических отношений преимущественно выступают производители сельскохозяйственной продукции или ее переработчики; в-третьих, содержание биоэнергетических отношений заключается в производстве и переработке сельскохозяйственной продукции. То есть биоэнергетические отношения на этапах производства (образования) биомассы и ее переработки в биотопливо составляют разновидность сельскохозяйственной деятельности, государственная поддержка которой регулируется агропротекционным правом. Выявлено, что с точки зрения государственной поддержки следует принимать такие меры, как: поддержка осуществления переработки собственно произведенной сельскохозяйственной продукции ее производителем; поддержка создания сельскохозяйственных перерабатывающих кооперативов; поддержка биоэнергетического производства, в основе которого лежит процесс переработки биомассы в биотопливо. Совершенствование агропротекционного законодательства в этой сфере должно происходить путем: а) предвидение универсальных механизмов поддержки перерабатывающей деятельности в Законе Украины «О государственной поддержке сельского хозяйства Украины"; б) дополнение Закона Украины «О сельскохозяйственной кооперации» агропротекционными положениями о сельскохозяйственных перерабатывающих кооперативах; в) принятие Закона Украины «О производстве и реализации биотоплива».
Hodovaniuk A. I. State support of bioenergy in Ukraine: legal problems / A. I. Hodovaniuk, K. A. Hryhorieva, Y. O. Platonova, O. V. Stepska, I. Y. Chumachenko // Amazonia Investiga. – V. 9 (25). - Universidad de la Amazonia, 2020. – Р. 15-23.
Keywords: bioenergy; biofuel production; agriculture; biomass; agroprotective law; state support; ecology; біоенергетика; виробництво біопалива; сільське господарство; біомаса; агропротекційне право; державна підтримка; екологія; биоэнергетика; производство биотоплива; сельское хозяйство; биомасса; агропротекционное право; государственная поддержка; экология; Research Subject Categories::LAW/JURISPRUDENCE